Answer:
see explanation
Explanation:
To find the solution without graphing means taking an algebraic approach.
Since both systems give y in terms of x equate the right sides, that is
(a)
x - 2 = - x + 8 ( add x to both sides )
2x - 2 = 8 ( add 2 to both sides )
2x = 10 ( divide both sides by 2 )
x = 5
substitute x = 5 into either of the 2 equations for corresponding value of y
y = x - 2 : y = 5 - 2 = 3
Solution is (5 , 3)
----------------------------------------------------------
(b)
- 3x = - 4x + 2 ( add 4x to both sides )
x = 2
substitute x = 2 into either of the 2 equations for y
y = - 3x : y = - 3 × 2 = - 6
Solution is (2, - 6)